ANALISIS DAERAH RAWAN KECELAKAAN (BLACKSPOT) DI JALAN TOL JAGORAWI - Andi Darmawan; Zainal Nur Arifin (Construction and Material Journal, 2020)
Traffic accidents are a problem, especially on toll roadsbecause toll roads are designed as highways with high levels of comfort, smoothness and safety The number of accidents on Indonesian toll roads is still high. This research is expected to be able to address the above problems, especially the identification of accident-prone locations (black spot), accident characteristics, and proposed treatment at black spot.  The location of the study was the Jagorawi Toll Road (2015 - 2017) for 49 Km. Identification of black spot used the Accident Equivalent Rate (AEK) method, and identified locations prone to accidents (black spot) on Jakarta - Ciawi route were Km 08 - 09, Km 22 - 31, Km 33 – 37, and Km 39 – 43, while on Ciawi - Jakarta, tracks were Km 04 - 09, Km 21 - 23, Km 28 - 29, Km 34 - 35, Km 40 – 41, and Km 44 - 45. Identification of accident characteristics using data approach analysis and statistical analysis were fine weather, one-lane, 00.00 - 06.00, lack of anticipation, self-accident and mini bus. The proposed handling of accident-prone locations (black spot) to reduce the number of accidents is by Minimum Service Standards (MSS) of toll road safety, such as traffic signs, street lighting, rumble strips and other toll road safety equipment. Keywords : Black Spot, Equivalent Accident Number, Accident Characteristics.